Perceived stress level is associated with coronary artery disease severity in patients with ST-segment elevation myocardial infarction - Serkan Kahraman; Fatma Cam Kahraman; Hicaz Zencirkiran Agus; Ali Kemal Kalkan; Fatih Uzun; Muammer Karakayalı; Mehmet Altunova; Samet Sevinç; Ali Rıza Demir; Emre Yılmaz; Mehmet Ertürk (KARE Publishing, 2020)
Objective: Stress is known to be a significant risk factor for coronary atherosclerosis and adverse cardiovascular events; however, the stress-related coronary atherosclerotic burden has not yet been investigated. The aim of this study was to investigate the relationship between the Perceived Stress Scale (PSS) and the SYNTAX scores in patients with ST-segment elevation myocardial infarction (STEMI). Methods: A total of 440 patients with STEMI were prospectively enrolled and divided into 2 groups according to the PSS score with a ROC curve analysis cut-off value of 17.5. In all, 361 patients with a low PSS score were categorized as Group 1 and 79 patients with a high PSS score were categorized as Group 2. Results: The SYNTAX score [Group 1, 16.0 (10.0-22.5); Group 2, 22.5 (15.0-25.5); p<0.001] and the SYNTAX score II were significantly higher in Group 2 [Group 1, 24.8 (19.0-32.6); Group 2, 30.9 (22.3-38.9); p<0.001]. Spearman analysis demonstrated that the PSS score was associated with the SYNTAX score (r=0.153; p=0.001) and the SYNTAX score II (r=0.216; p<0.001). Additionally, the PSS (odds ratio: 2.434, confidence interval: 1.446-4.096; p=0.001) was determined to be an independent predictor of a moderate-to-high SYNTAX score. The PSS score of patients with in-hospital mortality was also higher than those who survived [15 (10-20); 9 (4-16), respectively; p=0.007]. Conclusion: Stress appears to accelerate the coronary atherosclerotic process and the associated burden. An increased stress level was found to be an independent predictor of a high SYNTAX score.